Optimizing Interdisciplinarity in Data Analysis with the Adapted Alpha-Power Transformation of the Nadarajah-Haghighi Distribution (CSIAM Transactions on Applied Mathematics, 2025)
The practice of incorporating extra parameters into standard models is a common technique in statistical analysis. Adding an extra parameter enables the formation of a new model by applying the modified alpha-power transformation, employing the Nadarajah-Haghighi model as the baseline. Numerous characteristics of the said model are acquired, like the mode, quantiles, entropies, stochastic orders, mean residual life function, and order statistics. The maximum likelihood estimation method has been employed to estimate the parameters of the suggested model. To show how well the suggested distributions will function in a real-world setting, a simulation study has also been carried out and data has been examined. It is attained that the proposed model outperforms several other cutting-edge, current models as well as the baseline.
Keywords: Modified alpha-power transformation; Nadarajah-Haghighi; characteristic function; simulation study; real data sets